THE CHARACTERIZATION OF STAPHYLOCOCCAL TOXINS : I. THE ELECTROPHORETIC MIGRATION OF THE ALPHA HEMOLYTIC, DERMONECROTIC, LETHAL AND LEUCOCIDAL ACTIVITIES OF CRUDE TOXIN - Kumar, Surendra (The Rockefeller University Press, 1962)
The continuous flow paper electrophoretic methods used to isolate alpha hemolysin are presented. The purity of the alpha hemolysin preparation is demonstrated by double agar diffusion, immunoelectrophoretic, and ultracentrifugation techniques. Indirect evidence of purity is provided by the fact that rabbits immunized with purified alpha hemolysin produced detectable antibody only to alpha hemolysin. Direct support is given to the "unitarian theory" by the demonstration that purified alpha hemolysin also possessed dermonecrotic, lethal, and leucocidal activities. Further studies dependent on the availability of purified alpha hemolysin are outlined.